The Role of Emotions in Teacher Agency: A Study of Mexican English Language Educators - Héctor Castro Mosqueda (Profile Issues in Teachers' Professional Development)
This exploratory study examines the link between emotions and teacher agency across different geographical contexts. Semi-structured interviews and life stories were used and analyzed through Hargreaves’ emotional geography framework. The findings reveal that emotions significantly influence the teachers’ ability to manage classroom dynamics and implement positive changes. The research underscores the importance of empathy, ethics, and conflict resolution in building strong student relationships and supportive learning environments. It advocates for integrating emotional intelligence, empathy, and ethical decision-making into language teacher education programs to enhance teacher development and promote more inclusive, effective educational settings.